PERBAIKAN RANCANGAN MEKANISME PENGUNCI KOTAK CETAKAN BUSA JOK SEPEDA MOTOR - Tono Sukarnoto; Jamal M Afiff; Nora Azmi; Sentot Noviato (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
UD Anugerah Mulia produces aftermarket motorcycle seat foam. The production process is carried out manually by pouring the dough into the mold and allowing it to expand so that it follows the shape of the mold. This PKM activity is focused on the problem of damage to the mold box lock that occurs quite often. If the lock is damaged the mold box cannot be used and must be replaced with another box, so there is a delay in replacing the mold box. The purpose of this PKM is to improve the design of the locking system to make it more reliable and easy to operate. The existing locking system requires the foot of the operator to open and lock the mold cover. The force due to these shocks is often too strong so that the locking components are broken or damaged. The method of implementing this community service activity is carried out through a survey at the PKM target location, namely the UD Anugerah Mulia workshop in Jatiraden Jatisampurna, Bekasi City. From the analysis of the solution search, it was found that the design of the locking system was improved using a pair of pneumatic cylinders. This system does not require an operator to lock and unlock so it is expected to be more durable and reliable.